Molecular Modelling of Potential Candidates for the Treatment of Depression. Issue 7 (27th May 2019) - Silva, Daniela Rodrigues; Barigye, Stephen J.; Santos‐Garcia, Letícia; Fontes Ferreira da Cunha, Elaine
Abstract: A lot of research initiatives in the last decades have been focused on the search of new strategies to treat depression. However, despite the availability of various antidepressants, current treatment is still far from ideal. Unwanted side effects, modest response rates and the slow onset of action are the main shortcomings. As a strategy to improve symptomatic relief and response rates, the dual modulation of the serotonin transporter and the histamine H3 receptor by a single chemical entity has been proposed in the literature. Accordingly, this work aims to elucidate key structural features responsible for the dual inhibitory activity of the hexahydro‐pyrrolo‐isoquinoline derivatives. For this purpose, two approaches were employed, four‐dimensional quantitative structure‐activity relationship (4D‐QSAR) and molecular docking. The 4D‐QSAR models for both receptors allowed the identification of the pharmacophore groups critical for the modelled biological activity, whereas the binding mode of this class of compounds to the human serotonin transporter was assessed by molecular docking. The findings can be applicable to design new antidepressants. Abstract :